ANALYSIS OF THE ROLE OF MEDIA IN TRANSNATIONAL MOVEMENT, TEMPO INVESTIGATION AGAINST PANAMA PAPERS POLICY IN INDONESIA - muhammad irfan al amin (: 2621-0924)
This paper seeks to analyze the role of Tempo as a media and transnational movement actor in investigating the Panama Papers case, which involves high-ranking state officials in Indonesia. In this discussion will use media framing analysis, divided into two major dimensions of problem selection and emphasis on certain aspects of reality. Because Tempo is a transnational movement actor having an influence on domestic policy in Indonesia, there needs to be a study that uses the Boomerang Pattern method so that it can show the influence of its investigative efforts in finding news not only done alone, but also get help from other international media that has an important role such as in obtaining data access, information dissemination and media publications. Investigation of this news also shows that the media can have a real effect on government policy in a country.Keywords: Tempo, Media, Panama Papers, Transnational Movement.